Changes in Pediatric Portal Use Among Caregivers Before, During, and After the Coronavirus Disease 2019 Pandemic: A Longitudinal Study - Haessner, Philipp; Ray, Jessica M.; Gregory, Megan E. (Applied Clinical Informatics, 2025)
Patient portals are increasingly used to support digital health engagement, but little is known about how caregivers used patient portals before, during, and after the coronavirus disease 2019 (COVID-19) pandemic.This study aimed to examine longitudinal changes in caregiver engagement with pediatric patient portals, focusing on logins, session duration, messaging behaviors, and provider response times across prepandemic, pandemic, and postpandemic periods.We conducted a retrospective cohort study using deidentified MyChart data from caregivers of children aged 0 through 11 who received care at four pediatric primary care clinics in the Southeastern United States between March 2018 and March 2023. Generalized linear models were used to compare portal engagement across prepandemic, pandemic, and postpandemic periods. Outcomes included login frequency, session duration, message volume, message types and recipients, and provider response times, all normalized per user per year.Among 478 caregivers, portal logins and session duration increased significantly during and postpandemic, with 16-fold increases postpandemic compared with prepandemic (p < 0.001). Message volume declined substantially during the pandemic (p < 0.001) but returned to baseline levels. Provider response times shortened during the pandemic and remained lower than prepandemic levels (p = 0.032). Messaging to primary care declined and did not recover fully, while specialty care messaging increased across all periods. Appointment and medical advice messages declined during the pandemic, with only the latter rebounding. Customer service inquiries rose significantly and remained elevated, and medication renewal messages increased markedly postpandemic.The COVID-19 pandemic initiated lasting changes in caregivers' engagement with pediatric patient portals, including deeper engagement, quicker provider responses, and shifts in messaging patterns. Findings can be used to guide and optimize caregiver-centered digital health strategies in pediatrics. Future work should explore potential provider burnout from increased portal workload, incorporate multicenter studies, and link portal use to clinical characteristics to better inform digital health interventions.
Keywords: patient portal; MyChart; electronic medical record; pediatrics; caregiver; COVID-19; telemedicine and telehealth; digital health